Production Capacity Planning Strategy to Deal with Seasonal Demand in the Food and Beverage Industry - aulya, Nia (Generasi Sains Indonesia, 2024)
This study aims to analyze the effectiveness of production capacity planning strategies in managing seasonal demand fluctuations in the food and beverage industry. Seasonal variability often presents challenges such as stockouts and operational inefficiencies, requiring companies to adopt flexible strategies to optimize production. The research employs a descriptive-quantitative design, surveying industry professionals and analyzing operational data from 10 food and beverage companies. Key strategies evaluated include Flexible Manufacturing Systems (FMS), advanced forecasting techniques, and supplier collaboration, focusing on their impact on production volume, lead time, and inventory turnover. Results show that companies implementing FMS and advanced forecasting achieved significant improvements in production volume (50% increase) and lead time reduction (up to 50%). Multivariate analysis of variance (MANOVA) confirmed that advanced forecasting and FMS had the most substantial effects on operational efficiency during peak demand periods. These findings underscore the importance of integrating flexible systems and predictive analytics in capacity planning to enhance responsiveness and mitigate seasonal demand challenges.